Innovative, rapid, high-throughput method for drug repurposing in a pandemic—A case study of SARS-CoV-2 and COVID-19 - Bello, Shaibu Oricha; Yunusa, Abdulmajeed; Adamu, Adamu Ahmed; Imam, Mustapha Umar; Bello, Muhammad Bashir; Shuaibu, Abdulmalik; Igumbor, Ehimario Uche; Habib, Zaiyad Garba; Popoola, Mustapha Ayodele; Ochu, Chinwe Lucia; Bello, Aishatu Yahaya; Deeni, Yusuf Yahaya; et al. (Frontiers in Pharmacology, 2023)
Several efforts to repurpose drugs for COVID-19 treatment have largely either failed to identify a suitable agent or agents identified did not translate to clinical use. Reasons that have been suggested to explain the failures include the use of inappropriate doses, that are not clinically achievable, in the screening experiments, and the use of inappropriate pre-clinical laboratory surrogates to predict efficacy. In this study, we used an innovative algorithm, that incorporates dissemination and implementation considerations, to identify potential drugs for COVID-19 using iterative computational and wet laboratory methods. The drugs were screened at doses that are known to be achievable in humans. Furthermore, inhibition of viral-induced cytopathic effect (CPE) was used as the laboratory surrogate to predict efficacy. Erythromycin, pyridoxine, folic acid, and retapamulin were found to inhibit SARS-CoV-2-induced CPE in Vero cells at concentrations that are clinically achievable. Additional studies may be required to further characterize the inhibitions of CPE and the possible mechanisms.